Experimental investigation on removal of suspended particles from water using flax fibre geotextiles. Issue 23 (2nd December 2017) - Abbar, Bouamama; Alem, Abdellah; Pantet, Anne; Marcotte, Stéphane; Ahfir, Nasre-Dine; Duriatti, Davy
ABSTRACT: Natural geotextiles are increasingly used in geotechnical applications such as bank protection and short-term soil reinforcement. This study aimed to highlight the behaviour of natural flax fibre geotextiles towards the retention of suspended particles ( SP ) present in urban runoff and often polluted. Indeed, it is well known that a large fraction of the heavy metals are often associated with the SP . Long-term filtration tests were performed on four laboratory filter designs. The objective was to study the influence of a nonwoven flax fibre geotextiles on SP transfer through a sandy porous media under saturated conditions. The experiments consisted of injecting SP in a column filled with sand with and without flax fibre geotextiles at a constant flow rate. The results showed that nonwoven flax fibre geotextiles can increase flow homogeneity. Retention efficiency of SP at column scale as well as spatial deposition profile was modified by the presence of geotextile. The use of flax fibre geotextiles increases considerably the durability of the filtration system. Particle size analysis of the particles retained in the sand medium and in geotextiles shows that the coarser particles are mainly deposited at the entrance of the column, and in the geotextiles.